Bunso (The Youngest) (Ditsi Carolino) - Paculdar, Ma. Agnes A. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of the film Bunso (The Youngest), directed by Ditsi Carolino.
Keywords: bunso; child prisoners